2016
DOI: 10.1093/ecco-jcc/jjv234
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumour Necrosis Factor α Therapies and Inflammatory Bowel Disease Pregnancy Outcomes: A Meta-analysis

Abstract: Background and Aims: Inflammatory bowel disease (IBD) commonly affects women during their reproductive years, leading to concerns regarding pregnancy outcomes and therapeutic safety. The aim of this study was to assess the risks associated with anti-tumour necrosis factor α (anti-TNFα) therapy for pregnancy outcomes, including rates of congenital abnormality, based on published studies. Methods: Published studies were screened from on-line databases and international meeting abstracts. A meta-analysis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 78 publications
2
52
0
2
Order By: Relevance
“…Tumour necrosis factor (TNF) antagonists have the most data available, with several reports of safe use, although etanercept has been associated with an increased risk of spontaneous abortion in the first trimester . A recent meta‐analysis of 482 patients with IBD exposed to TNF antagonists during pregnancy did not find any association with adverse pregnancy outcomes (pooled OR 1·14, 95% CI 0·73–1·78; P = 0·55) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumour necrosis factor (TNF) antagonists have the most data available, with several reports of safe use, although etanercept has been associated with an increased risk of spontaneous abortion in the first trimester . A recent meta‐analysis of 482 patients with IBD exposed to TNF antagonists during pregnancy did not find any association with adverse pregnancy outcomes (pooled OR 1·14, 95% CI 0·73–1·78; P = 0·55) …”
Section: Discussionmentioning
confidence: 99%
“…26 A recent meta-analysis of 482 patients with IBD exposed to TNF antagonists during pregnancy did not find any association with adverse pregnancy outcomes (pooled OR 1Á14, 95% CI 0Á73-1Á78; P = 0Á55). 28…”
Section: Discussionmentioning
confidence: 99%
“…Shihab, Yeomans, and De Cruz () performed a systematic review and meta‐analysis of the available literature on the exposure of anti‐TNF therapy in pregnant women with inflammatory bowel disease. They did not find an increase of adverse pregnancy outcomes, congenital abnormalities, premature birth or low birth weight compared with disease‐matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…These diseases share common genetics involved and the balance between the cytokines Th17 and Tregs, which allows a certain comparison (Skroza, Proietti, & Pampena, 2013). Shihab, Yeomans, and De Cruz (2016) performed a systematic review and meta-analysis of the available literature on the exposure of anti-TNF therapy in pregnant women with inflammatory bowel disease.…”
Section: Year Of Deliverymentioning
confidence: 99%
“…Many studies and publications on pregnancies under IFX treatment have shown no indications of elevated malformation risks [25, 5153]. …”
Section: Biologics: Tnf-α Inhibitorsmentioning
confidence: 99%